THE IMPACT OF DISTANCE ON WILLINGNESS TO EAT OUT: EVIDENCE FROM SAMARKAND, UZBEKISTAN - Makhmadieva, Charos; Turdibekov, Khasan; Amiriddinova, Muslima; Toyirova, Shokhista; Yuldosheva, Latofat; Mahmudova, Zarrina; Abdukhamidov, Sarvar; Makhmudova, Aziza; Rofeeva, Rukhshona; Vafokulova, Mekhruza; Bakri, Rizal; Sobirov, Bobur (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigates the determinants influencing participation in gastronomic tourism in Samarkand, Uzbekistan, focusing on the role of distance, price satisfaction, and demographic characteristics. Using data collected from 303 respondents, logistic regression and decision tree analyses were applied to assess key behavioral predictors of culinary travel. The results reveal that distance is the most significant factor influencing willingness to engage in gastronomic tourism—individuals willing to travel farther are substantially more likely to seek authentic food experiences. In contrast, satisfaction with food prices and demographic factors such as age, gender, and expenditure levels were found to be statistically insignificant. These findings highlight that logistical accessibility outweighs demographic variables in shaping tourism participation. The study contributes to the literature by providing empirical evidence from an emerging destination, emphasizing the importance of mobility and access in gastronomic decision-making. Practical implications include the need for policymakers to improve transportation infrastructure, enhance culinary destination visibility, and promote authentic local food experiences. By strengthening these elements, Uzbekistan can better position itself as a prominent culinary tourism destination in Central Asia. The research also opens opportunities for future studies to explore psychological, cultural, and digital factors influencing food tourism behavior.